Checkpoint chemistry - Riley, Peter (Hodder Murray London, 2005)
Chapters are presented in the same order as topics in the Checkpoint Chemistry Scheme of Work; Chapters 1-5 are for Year 1, Chapters 6-10 for Year 2 and Chapters 11-15 for Year 3. The clear text and colourful illustrations and photographs fully explain the concepts and encourage background reading. Boxed sections are used to show how scientific ideas have developed over time and how they are applied in today's world. Questions throughout encourage pupils to extract relevant information from text and think more deeply about the topics. 'For discussion' boxes are designed specially to stimulate class or group discussions and can be used in work on science and citizenship. The extensive glossary contains all key syllabus words for chemistry and helps to build pupils' scientific vocabulary. The accompanying Teacher's Resource Book provides full support, including details of practical work, answers to all questions in the Pupil's Book and suggestions for the use of ICT.